Optimalisasi Kinerja Karyawan: Hubungan Motivasi Kerja, Pembinaan Disiplin, dan Persepsi Atasan di Departemen Human Resource Pada PT. X - Sari, Sukma Kumala; Mulyana, Aam Rachmat (Universitas Batanghari, 2024)
The decline in employee performance in terms of employee performance appraisal aspects of PT X company still has to be improved, especially in terms of processing time and conformity to standards in work, this is expected to increase if work motivation and discipline coaching are improved. The purpose of this study was to see respondents' responses about work motivation and employee discipline coaching on performance. The Human Resource Department of PT X is in good criteria. The sample used was 37 respondents and direct supervisors in the Human Resource Department. In the sampling technique, a saturated sampling method was used, and the data was analyzed using multiple linear regression. The results of this study indicate that work motivation does not have a positive effect on employee performance. However, employee discipline development has a positive effect on employee performance. Additionally, work motivation and discipline development simultaneously affect employee performance at PT. X.